2008
DOI: 10.1124/jpet.107.133306
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Splicing Caused by Single Nucleotide Polymorphism c.516G>T [Q172H], a Marker of CYP2B6*6, Is Responsible for Decreased Expression and Activity of CYP2B6 in Liver

Abstract: CYP2B6 is a polymorphic human drug metabolizing cytochrome P450 with clinical relevance for several drug substrates including cyclophosphamide, bupropion, and efavirenz. The common allele CYP2B6*6 [c. 516GϾT, Q172H, and c.785AϾG, K262R] has previously been associated with lower expression in human liver and with increased plasma levels of efavirenz in human immunodeficiency virus patients, but the molecular mechanism has remained unclear. We present novel data showing that hepatic CYP2B6 mRNA levels are reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
184
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(195 citation statements)
references
References 31 publications
9
184
1
1
Order By: Relevance
“…Data regarding the functional activity of CYP2B6.9 are said to be rare . In a COS-1 system, the activities of CYP2B6.6 and CYP2B6.9, in which 516G.T is the common polymorphism, were both extremely low, but this was attributed to minimal expression (Hofmann et al, 2008). CYP2B6.9 activity toward artemether was somewhat lower than CYP2B6.1 in COS-7 cells (Honda et al, 2011), and toward 7-ethoxy-4-trifluoromethylcoumarin, bupropion, and efavirenz in a reconstituted bacterial expression system (Zhang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data regarding the functional activity of CYP2B6.9 are said to be rare . In a COS-1 system, the activities of CYP2B6.6 and CYP2B6.9, in which 516G.T is the common polymorphism, were both extremely low, but this was attributed to minimal expression (Hofmann et al, 2008). CYP2B6.9 activity toward artemether was somewhat lower than CYP2B6.1 in COS-7 cells (Honda et al, 2011), and toward 7-ethoxy-4-trifluoromethylcoumarin, bupropion, and efavirenz in a reconstituted bacterial expression system (Zhang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical consequences of CYP2B6 allelic variants will depend on both the intrinsic activity of the mutant protein and its level of expression. The CYP2B6*6 allele causes low human hepatic CYP2B expression (Lang et al, 2001;Desta et al, 2007;Hofmann et al, 2008), thus both deficient catalytic efficiency and decreased P450 content combine to cause a diminished CYP2B6 metabolizer phenotype in CYP2B6*6 carriers. Liver microsomes from CYP2B6*6 carriers had diminished methadone Ndemethylation (Gadel et al, 2013).…”
Section: Downloaded Frommentioning
confidence: 99%
“…It should be noted that none of the aforementioned studies characterized CYP2B6 activity in their samples. Several other studies have found no difference in CYP2B6 expression or activity in relation to age; however, each of these studies included only a few pediatric microsomal samples between the ages of 2 and 18 in their sample set (Hesse et al, 2004;Parkinson et al, 2004;Desta et al, 2007;Hofmann et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies noted marked interindividual variability in CYP2B6 expression and activity in human livers; in vitro CYP2B6 mRNA expression (Lamba et al, 2003;Hofmann et al, 2008), protein levels (Hesse et al, 2004) and activity (Croom et al, 2010) have all been reported to exceed 250-fold. This remarkable variation in CYP2B6 expression and activity has the potential to result in therapeutic and toxic responses to medications metabolized by this enzyme, particularly for those drugs with narrow therapeutic indices.…”
Section: Introductionmentioning
confidence: 99%
“…42 Moreover, the common allele with a G-to-T substitution at nucleotide 516 (516G>T; rs3745274) is associated with lower expression via aberrant splicing events, 43 and the amino acid substitution of leucine to phehenylalanine at position 264 (Leu264Phe) has been reported to have functional consequences on CYP2B6 activity. 44 This is quite interesting because CYP2B6 and CYP3A4 are the main isoforms involved in metabolizing methadone and sibutramine (CYP2B6 only), and it is thought that part of the individual response to these drugs depends on genetic variants of these cytochromes. [45][46][47] The recent results of genetic association tests for CYP2D6, CYP2B6 and CYP2C19 variations are presented in Table 1.…”
Section: Cytochrome P450mentioning
confidence: 99%